The Efficacy of Dog Assisted Therapy in depression and anxiety – a review - Marciniuk, Dominika; Głogowska, Paulina; Grela, Wiktor; Niewiadomska, Jagoda; Gniaź, Natalia; Tulej, Dawid; Marko, Natalia; Dziedzic, Alicja; Furtak, Daria; Górska, Aleksandra (Journal of Education, Health and Sport, 2025)
Introduction: Animal-assisted-therapy (AAT) is a form of psychotherapy where animals are used as a part of a therapeutic process. Most commonly chosen are dogs and horses, however, some research shows a positive impact in therapy with farm animals, cats, birds, rodents, and dolphins. AAT provides a comfortable environment which empowers patients to recall traumatic memories and facilitates communication with their therapist. Furthermore, contact with therapeutic animals lowers blood pressure, heart rate and cortisol level. There have also been noted significant increases in beta-endorphin, oxytocyn, β-phenylethylamine and dopamine levels. Purpose: The purpose of this article was to present the current state of knowledge regarding the influence of dog-assisted therapy in individuals of all ages experiencing depression or anxiety. Material and methods: A review of the available literature was conducted by searching the PubMed, and Google Scholar databases using the keywords: adults, elderly, children, DAT, dog-assisted therapy, depression, anxiety. Included articles were published after the year 2000. Results: The studies reviewed consistently demonstrate the potential benefits of dog-assisted therapy (DAT) for alleviating anxiety, depression, and enhancing overall well-being in various populations. In dental and hospital settings, DAT significantly reduced anxiety and physiological distress with notable improvements in heart rate and depression scores. Conclusion: Dog-assisted therapy (DAT) effectively reduces anxiety and depression, demonstrating its potential as an engaging intervention for diverse populations. These findings support its broader integration into mental health programs.